L'orientamento e la formazione degli insegnanti del futuro - MARIANI, ALESSANDRO (Studi e saggi, 2014)
The volume examines the crucial and current connection between orientation, training and teaching professionalism. The various contributions make references to the new regulation on the subject, and focus on the institutional task and the pedagogical role played by orientation and training in creating a new physiognomy of the teachers' professionalism: an initial orientation, an in itinere orientation and an outgoing orientation, alongside personal and professional training, intended as an open and ongoing process. These are two fundamental devices to grasp the complexity of being a teacher and working in schools nowadays. They are also accompanied by the traineeship, which in this context is examined through the report of a multi-year work.